Adaptive noncommunication protection of double-circuit line systems. - Bo, Z.Q.
This paper presents a new technique for noncommunication protection of double-circuit lines. In the technique, the sequence and superimposed signals are used to detect the remote circuit breaker (CB) operation, from which it is to be determined whether a fault inside the protected section can be derived. Extensive simulation studies with respect to typical double-circuit transmission-line systems show that the proposed technique is able to rapidly and correctly determine whether a fault is inside the protected line section without the need for communication links.
Keywords: Adaptive noncommunication protection; Double-circuit line systems; Double-circuit transmission-line systems; Remote circuit breaker operation; Sequence signals; Superimposed signals